2018
DOI: 10.17341/gazimmfd.406781
|View full text |Cite
|
Sign up to set email alerts
|

Saldırı Tespit Sistemlerinde Genetik Algoritma Kullanarak Nitelik Seçimi ve Çoklu Sınıflandırıcı Füzyonu

Abstract: Sınıflandırıcı füzyonu ile birlikte nitelik seçme yapılmıştır  Nitelik seçme ve sınıflandırıcı füzyonu için genetik algoritmalar kullanılmıştır

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The training speed has been improved by adapting the parallel computing to the DBN training process in order to achieve global optimization with the genetic algorithm and to achieve more successful results in diagnosis accuracy. Özgür and Erdem [24] have used genetic algorithm in intrusion detection systems. In this study, it is suggested that feature selection and classifier fusion weight determination in intrusion detection classification applications need to be performed by using genetic algorithm (GA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The training speed has been improved by adapting the parallel computing to the DBN training process in order to achieve global optimization with the genetic algorithm and to achieve more successful results in diagnosis accuracy. Özgür and Erdem [24] have used genetic algorithm in intrusion detection systems. In this study, it is suggested that feature selection and classifier fusion weight determination in intrusion detection classification applications need to be performed by using genetic algorithm (GA).…”
Section: Literature Reviewmentioning
confidence: 99%